The Trace Conditional Learning of the Noxious Stimulus in UWS Patients and Its Prognostic Value in a GSR and HRV Entropy Study - Cortese, Daniela; Riganello, Francesco; Arcuri, Francesco; Lucca, Lucia; Tonin, Paolo; Schnakers, Caroline; Laureys, Steven (Frontiers in Human Neuroscience, 2020)
The assessment of the consciousness level of Unresponsive Wakefulness Syndrome (UWS) patients depends frequently by a subjective interpretation of the observed spontaneous and volitional behaviour. To date the misdiagnosis is around 30%. The aim of this study was to observe the behaviour of UWS patients, during the administration of noxious stimulation by a Trace Conditioning protocol, assessed by the Galvanic Skin Response (GSR) and Heart Rate Variability (HRV) entropy. We recruited 13 Healthy Control (HC) and 30 UWS patients at 31±9 days from the acute event evaluated by Coma Recovery Scale–Revised (CRS-R) and Nociception Coma Scale (NCS). Two different stimuli (musical stimulus (MUS) and nociceptive stimulus (NOC)), preceded respectively by 2 different tones, were administered following the sequences A) MUS1 – NOC1- MUS2 – MUS3 – NOC2 – MUS4 – NOC3 – NOC*, and B) MUS1*, NOC1*, NOC2*, MUS2*, NOC3*, MUS3*, NOC4*, MUS4*. All the (*) indicate the only tones administration. CRS-R and NCS assessments were repeated for 3 consecutive weeks. MUS4, NOC3 and NOC* were compared for GSR wave peak magnitude, time to reach the peak and time of wave’s decay by Wilcoxon’s test to assess the Conditioned Response (CR). The Sample Entropy (SampEn) was recorded in baseline and both sequences. Machine Learning approach was used to identify a rule to discriminate the CR. The GSR magnitude of CR was higher comparing music stimulus (p<0.0001) and CR extinction (p<0.002) in 9 patients and in HC. Patients with CR showed a higher SampEn in sequence A compared to patients without CR. Within 3rd and 4th weeks from protocol administration, 8 patients (88.9%) evolved into MCS. The Machine-learning showed a high performance to differentiate presence/absence of CR (≥95%). The possibility to observe the CR to the noxious stimulus, by means of the GSR and SampEn, can represent a potential contribute to reduce the misdiagnosis in UWS patients.